PRELIMINARY STUDIES ON PROBIOTIC POTENTIAL OF SELECTED LACTOBACILLUS VIT SSV STRAINS SCREENED FROM CURD SAMPLES OF VELLORE, BIHAR HARYANA AND VARANASI - SANJEEB KUMAR MANDAL,; SUNEETHA VUPPU, (International Journal of Pharma and Bio Sciences, 2013)
Curd, Dahi or perugu is a potential source of probiotic Lactobacilli. In the present study, four different strains of Lactobacillus spp. were isolated from curd in different regions like Vellore ,Varanasi, Haryana, Bihar which were subjected to preliminary screening and characterization and further examined for the presence of probiotic properties and differentiated on the basis of biochemical testing and growth kinetics. Different Lactobacillus strain produces a different concentration of lactic acid which depends on strain and ecological diversity. By titration method we got the concentration of the lactic acid in different sample. Cultures were subjected to characterize its antioxidant activity. No scientific evaluation of the antioxidant activity of Lactobacillus from curd sample has been reported so far. Therefore, it was thought worthwhile to evaluate the antioxidant activity of Lactobacillus. Acid tolerance of the cultures with microbial and ecological diversity was studied by incubating the organisms in MRS broth. The NaCl tolerance and bile tolerance of the isolated microbial strains were evaluated which indicate its probiotic potential.